Gambaran Kemampuan Berpikir Kritis Siswa Sekolah Dasar Saat Pandemi Serta Implikasinya Dalam Bimbingan Dan Konseling - Andriani, Miranti Widi (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2021)
The purpose of the curriculum is to want learning and learning outcomes, one of which is to develop the potential for critical thinking. Especially in elementary schools, critical thinking skills are still mandatory to be prioritized during the learning and learning process. Since the pandemic, there has been a change in the implementation of learning from direct to distance learning. It is very important to know the description of students' critical thinking skills, especially in elementary schools and during a pandemic so that they can make improvements in learning methods and prepare guidance steps. This research uses descriptive quantitative method which aims to describe critical thinking skills. The data collection technique used a non-test technique by giving a critical thinking scale questionnaire. The data analysis technique was to describe the data using descriptive statistics. The results of the study show that the critical thinking ability of elementary school students during the pandemic is in the fairly critical category. The breakdown of the percentage gain for each indicator is that elementary clarification shows a fairly critical result, basic support shows a fairly critical result, inference shows a non-critical result, advance clarification shows a non-critical result, and tactics and strategy shows a fairly critical result. The results of the research are expected to be used as recommendations to teachers as actors of guidance and counseling in curative treatment steps for elementary school students so that they can help students develop optimally.